New insights into structure and replication of the Hepatitis C virus and clinical implications - Pönisch, Marion; Bartenschlager, Ralf (Seminars in liver disease, 2010)
With the advent of efficient systems to propagate the hepatitis C virus (HCV) in cultured cells important new discoveries have been made. For instance, several molecules required for HCV infection of hepatocytes have been identified and first insights into the entry pathway have been gained. Ribonucleic acid (RNA) replication and virion assembly were found to be tightly linked to lipid metabolism and numerous host factors contributing to viral replication have been identified. Some of them such as cyclophilin A or microRNA-122 are attractive targets for antiviral therapy as are the viral serine-type protease residing in nonstructural protein 3 (NS3) and the NS5B RNA-dependent RNA polymerase. More recently, the viral phosphoprotein NS5A emerged as an additional and very promising target for selective therapy. These results illustrate the great progress that has been made in the HCV field and how this knowledge can be used to devise innovative strategies to counteract this pathogen.